Survey of the Relationship Between Student Learning Independence and Scientific Learning Outcomes Islamic Junior High School (Madrasah Tsanawiyah) in South Jakarta - Fitri Awaliyah (Universitas Islam Negeri (UIN) Mataram, 2022)
The purpose of this study was to clarify the relationship between student learning independence and scientific learning outcomes. The method used in this survey is a survey. The population of this survey was class VIII Madrasah Tsanawiyah Negeri in South Jakarta, for a total of 720 students, and the sample size of this survey was 88 students. Sampling was performed using a combination of clustering, proportional, and random techniques. This survey data collection is in the form of a survey using the Likert scale model that respondents need to fill out and a data analysis using the SPSS 20 program. The result is a value of Sig = 0.000 < 0.05 and tcount = 3.727, H0 is discarded. This means that student learning independence is actively associated with scientific learning outcomes.